Puerperal sepsis caused by liver abscess: case report - Flávio Xavier Silva; Alex Sandro Rolland Souza
Abstract Introduction: sepsis is a serious public health problem, affecting millions of people in the world each year, with a high mortality rate (one out of four patients) and an increasing incidence. Sepsis is one of the main causes of maternal mortality and an important cause of admission to obstetric intensive care units. Case description: In this study, the authors report the case of a woman having been submitted to cesarean section three days before presenting clinical signs of sepsis and septic shock caused by a liver abscess. The patient had a set of complications secondary to shock, such as thrombocytopenia, coagulopathy, toe ischemia and acute kidney failure. The patient had cholelithiasis and recurrent pain in the right hypochondrium during pregnancy. During hospitalization, the mechanism involved in the development of hepatic abscess was infection of the biliary tract. The patient was treated in an obstetric intensive care unit with antibiotics and drainage of the liver abscess. Progress was favorable and the patient was discharged in good health. Discussion: pyogenic liver abscess during pregnancy and puerperium is a serious condition which represents a diagnostic and therapeutic challenge, with few cases reported. The normally nonspecific clinical and laboratory findings can lead to a late diagnosis, which increases the risk of maternal morbidity and mortality.